Aluminum hydroxide filled epoxy resin for copper clad laminate and preparation method thereof
By adding aluminum hydroxide filled with aluminum hydroxide and polysiliconxane to the copper -covered plate to form a composite flame retardant, the problem of insufficient combustion and flame retardant performance of epoxy resin under high temperature conditions is solved. , Achieve efficient flame retardant and mechanical performance improvement.
Patent Information
- Application Number
- CN202410931816.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Existing epoxy resins for copper clad plates may burn or produce toxic gases under high temperature conditions, and the flame retardant performance is insufficient, which affects the safety of electronic equipment. Direct addition of flame retardant may reduce the mechanical properties of the material.
By preparing the nuclear shell flame retardant and polysiliconoxane filled with aluminum -filled aluminum, combined with epoxy resin, nuclear shell tough fillers, curing agent, etc., a composite flame retardant is formed to improve the flame retardant performance and mechanical performance of the material.
It significantly improves the flame retardant performance and mechanical performance of epoxy resin, can effectively suppress combustion under high temperature conditions, delay the spread of flames, and improve the safety of electronic equipment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminate preparation, in particular to aluminum hydroxide filled epoxy resin for copper clad laminate and a preparation method thereof. Background Art
[0002] Epoxy resin for copper clad laminate is a material widely used in the electronics industry, mainly used to manufacture printed circuit boards (PCBs). It has excellent properties, including good electrical insulation, chemical resistance, high mechanical strength and good processing properties. This enables epoxy resin to meet the requirements of modern PCBs for high density, high speed and high reliability. However, there are still some technical pain points in epoxy resin for copper clad laminate, especially in terms of flame retardancy. Although epoxy resin itself has certain flame retardancy, it may still burn or produce toxic gases under high temperature conditions. This poses a potential threat to the safety of electronic equipment, and the flame retardancy of the material needs to be further improved. However, the direct addition of flame retardants may lead to compatibility problems between fillers and epoxy resins, thereby reducing the mechanical properties of epoxy resin for copper clad laminates. Therefore, the key to solving this problem is to improve the particle shape and size of the filler and improve the interfacial adhesion between the filler and the resin. At the same time, it is also necessary to optimize the dispersion process to improve the thermal conductivity, toughness and adhesion of the material, as well as the dispersibility and stability. Through these improvement measures, the flame retardancy of epoxy resin for copper clad laminates can be improved while maintaining its original mechanical properties. This will help improve the safety of electronic devices and meet the requirements of the modern electronics industry for PCB materials. Therefore, continuous research and innovation are very important in the development of epoxy resin technology for copper clad laminates.
[0003] In order to overcome the defects of the prior art, the present invention provides an aluminum hydroxide filled epoxy resin for copper clad laminate and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide an aluminum hydroxide filled epoxy resin for copper clad laminate and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing an epoxy resin filled with aluminum hydroxide for a copper clad laminate comprises the following steps:
[0007] Step 1: Under an argon environment, mix the emulsifier and deionized water, stir evenly, then add n-butyl acrylate and 1,4-butanediol diacrylate, stir evenly, then add 1 / 6 mass part of initiator, react for 1-2 hours, then add 1 / 12 mass part of initiator, continue to react for 10-15 minutes, and obtain a seed polymerization emulsion; then drop the core layer pre-emulsion and 1 / 4 mass part of initiator into the seed polymerization emulsion, and the reaction time is 2-3 hours; after the dropwise addition, drop the shell layer pre-emulsion and 1 / 2 mass part of initiator, and the reaction time is 3-4 hours. After the reaction is completed, cool, filter, and dry at low temperature to prepare a core-shell toughened filler;
[0008] Step 2: In a nitrogen environment, the modified silane, dimethyldimethoxysilane and deionized water are mixed, refluxed at 25-30°C for 2-3h, heated to 90-100°C for further reaction for 5-5.5h, and cooled to 25-30°C after the reaction to obtain a hydrolyzate; then a catalyst and a capping agent are added, and the reaction is carried out at 100-110°C for 10-12h. After the reaction is completed, acetic acid is added dropwise for neutralization and low-boiling products are extracted to prepare polysiloxane;
[0009] Step 3: Mix aluminum hydroxide powder and 3 / 8 parts by weight of anhydrous ethanol, add phosphoric acid after mixing evenly, stir to react for 6-8 hours, filter, wash, and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 5 / 8 parts by weight of anhydrous ethanol, add polysiloxane, stir to react for 5-8 hours, filter, wash, and dry after the reaction to prepare a composite flame retardant;
[0010] Step 4: Mix the epoxy resin, composite flame retardant, core-shell toughening filler, curing agent, curing accelerator and solvent, and stir at high speed for 6-8 hours to prepare a finished product.
[0011] More optimally, in step one, the contents of each component of the core-shell toughening filler are: by mass, 0.5-0.8 parts of emulsifier, 150-200 parts of deionized water, 10-15 parts of n-butyl acrylate, 0.06-0.08 parts of 1,4-butanediol diacrylate, 120-480 parts of initiator, 153.7-185.9 parts of core layer pre-emulsion, and 41.8-53.0 parts of shell layer pre-emulsion.
[0012] More optimally, the core layer pre-emulsion is composed of 150-180 parts of n-butyl acrylate, 3-5 parts of emulsifier and 0.7-0.9 parts of cross-linking agent; the shell layer pre-emulsion is composed of 40-50 parts of methyl methacrylate monomer, 0.8-1.0 parts of emulsifier and 1-2 parts of functional monomer.
[0013] More optimally, the initiator is a mixture of potassium persulfate and deionized water in a mass ratio of (0.08-0.10):10; the crosslinking agent is allyl methacrylate; the functional monomer is acrylamide; and the emulsifier is sodium dodecyl diphenyl ether disulfonate.
[0014] More optimally, in step 2, the contents of the various components of the polysiloxane are: by mass, 20-40 parts of modified silane, 15-20 parts of dimethyldimethoxysilane, 20-40 parts of deionized water, 0.5-0.8 parts of catalyst, 0.4-0.6 parts of end-capping agent, and 0.8-1.0 parts of acetic acid; the catalyst is potassium hydroxide and the end-capping agent is hexamethyldisiloxane.
[0015] More optimally, the preparation method of the modified silane is: in a nitrogen environment, 1,3,5-trialdehyde-1,3,5-triazine, (3-aminopropyl)triethoxysilane and anhydrous ethanol are mixed, stirred and reacted at 60-70°C for 1-2 hours, and then rotary evaporated and vacuum dried to obtain a silane intermediate; in a nitrogen environment, the silane intermediate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and anhydrous ethanol are mixed, stirred and reacted at 90-100°C for 4-6 hours to obtain a modified silane.
[0016] More optimally, the reaction molar ratio of 1,3,5-trialdehyde-1,3,5-triazine, (3-aminopropyl)triethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:(4-5):3.
[0017] More optimally, in step three, the contents of the components of the composite flame retardant are: by mass, 15-20 parts of aluminum hydroxide powder, 40-70 parts of anhydrous ethanol, 10-15 parts of phosphoric acid, and 8-15 parts of polysiloxane.
[0018] More optimally, in step four, the contents of the components of the finished product are: by mass, 100-150 parts of epoxy resin, 20-30 parts of composite flame retardant, 15-25 parts of core-shell toughening filler, 10-15 parts of curing agent, 0.03-0.05 parts of curing accelerator, and 30-50 parts of solvent.
[0019] More optimally, the curing agent is methyl nadic anhydride, the curing accelerator is 2-phenylimidazole, and the solvent is acetone.
[0020] Beneficial effects of the present invention:
[0021] The present invention prepares a core-shell toughening filler by adding an emulsifier, deionized water, n-butyl acrylate, 1,4-butanediol diacrylate, an initiator, a core layer pre-emulsion and a shell layer pre-emulsion. Polysiloxane is prepared by adding modified silane, dimethyldimethoxysilane, deionized water, a catalyst, a capping agent and acetic acid. A core-shell flame retardant is prepared by adding aluminum hydroxide powder, anhydrous ethanol and phosphoric acid; and then the polysiloxane, the core-shell flame retardant and anhydrous ethanol are mixed to prepare a composite flame retardant. Finally, epoxy resin, composite flame retardant, core-shell toughening filler, curing agent, curing accelerator and solvent are mixed, and a finished product is prepared by high-speed stirring.
[0022] The present invention is characterized in that, in step 1, by adding an emulsifier, deionized water, n-butyl acrylate, 1,4-butanediol diacrylate, an initiator, a core layer pre-emulsion and a shell layer pre-emulsion, a core-shell toughened filler with poly n-butyl acrylate as a core layer and polymethyl methacrylate as a shell layer is prepared. The core-shell toughened filler is a high-strength filling material, which can significantly improve the toughness and mechanical properties of epoxy resin. By adding a reinforcing filler, the reduction in the mechanical properties of epoxy resin caused by adding a flame retardant can be compensated.
[0023] In step 2, 1,3,5-trialdehyde-1,3,5-triazine, (3-aminopropyl)triethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are used as main raw materials to prepare a modified silane. Then, modified silane, dimethyldimethoxysilane, deionized water, a catalyst, a capping agent and acetic acid are used as raw materials to prepare polysiloxane. Among them, 1,3,5-trialdehyde-1,3,5-triazine and (3-aminopropyl)triethoxysilane undergo nucleophilic addition to generate Schiff base, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and Schiff base undergo nucleophilic addition reaction to prepare modified silane. On the one hand, the modified silane prepared by the present invention contains more flame retardant elements such as nitrogen and phosphorus, which can inhibit the combustion reaction and slow down the flame spread rate by activating or adsorbing free radicals and combustion products; adding it to epoxy resin can effectively improve the flame retardant properties of the finished product; on the other hand, in step 2, polysiloxane is prepared with modified silane and dimethyldimethoxysilane as main raw materials, and silicon element usually has lower flammability and higher thermal stability, so it can effectively prevent or delay the combustion process; at the same time, the characteristics of silicon element participating in chemical reactions or physical bridging can be used to delay the combustion process through isolation, heat absorption, stabilization and other mechanisms.
[0024] In step three, by adding aluminum hydroxide powder, anhydrous ethanol and phosphoric acid, a core-shell flame retardant with aluminum hydroxide as the core and aluminum phosphate as the shell is prepared. Then polysiloxane, core-shell flame retardant and anhydrous ethanol are mixed, and a layer of polysiloxane is coated on the surface of the core-shell flame retardant to obtain a composite flame retardant. On the one hand, the flame retardant with a core-shell structure has a smaller size and particle size, has good compatibility with epoxy resin, and can maintain excellent mechanical properties while providing a good flame retardant effect. On the other hand, the polysiloxane prepared in step two is coated on the surface of the core-shell flame retardant prepared in step three to obtain a composite flame retardant. Among them, the core-shell flame retardant has good thermal stability and combustion inhibition performance, and then by coating polysiloxane, the flame retardant component of the material is increased, and on the basis of the core-shell flame retardant, the flame retardant effect is more obvious. Since polysiloxane and core-shell flame retardant have different flame retardant mechanisms, they can play a synergistic effect after compounding, thereby improving the overall flame retardant performance. The preparation method of this composite material is simple and practical, has good flame retardant effect, and is expected to be widely used in the field of fireproof materials. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Source of raw materials:
[0027] The curing agent is provided by Pandex (Shanghai) International Trading Co., Ltd., model number is 25134-21-8; the epoxy resin is provided by Shanghai Yantai E-Commerce Co., Ltd., model number is EP137.
[0028] Example 1: Step 1: 150 g of n-butyl acrylate, 3 g of sodium dodecyl diphenyl oxide disulfonate and 0.7 g of allyl methacrylate are mixed to prepare a core layer pre-emulsion; 40 g of methyl methacrylate monomer, 0.8 g of sodium dodecyl diphenyl oxide disulfonate and 1 g of acrylamide are mixed to prepare a shell layer pre-emulsion; 0.8 g of potassium persulfate and 100 g of deionized water are mixed to prepare an initiator;
[0029] In an argon environment, 0.5 g of sodium dodecyl diphenyl ether disulfonate and 150 g of deionized water were mixed, and after stirring, 10 g of n-butyl acrylate and 0.06 g of 1,4-butanediol diacrylate were added, and after stirring, 20 g of initiator was added, and after reacting for 2 hours, 10 g of initiator was added, and the reaction was continued for 15 minutes to obtain a seed polymerization emulsion; 153.7 g of the core layer pre-emulsion and 30 g of the initiator were added dropwise to the seed polymerization emulsion, and the reaction time was 3 hours; after the addition was completed, 41.8 g of the shell layer pre-emulsion and 60 g of the initiator were added dropwise, and the reaction time was 4 hours. After the reaction was completed, it was cooled, filtered, and low-temperature dried to prepare a core-shell toughened filler;
[0030] Step 2: Under a nitrogen environment, 0.1 mol of 1,3,5-trialdehyde-1,3,5-triazine, 0.4 mol of (3-aminopropyl)triethoxysilane and 300 ml of anhydrous ethanol were mixed, stirred at 70°C for 2 hours, and then subjected to rotary evaporation and vacuum drying to prepare a silane intermediate; under a nitrogen environment, the silane intermediate, 0.3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 300 ml of anhydrous ethanol were mixed, stirred at 100°C for 6 hours to prepare a modified silane;
[0031] Step 3: Under a nitrogen environment, 20 g of modified silane, 15 g of dimethyldimethoxysilane and 20 g of deionized water were mixed, refluxed at 30 ° C for 3 h, heated to 100 ° C and continued to react for 5.5 h, and cooled to 30 ° C after the reaction to obtain a hydrolyzate; then 0.5 g of potassium hydroxide and 0.4 g of hexamethyldisiloxane were added, and the reaction was carried out at 110 ° C for 12 h. After the reaction, 0.8 g of acetic acid was added dropwise to neutralize and remove low-boiling products to prepare polysiloxane;
[0032] Step 4: Mix 15g of aluminum hydroxide powder and 15g of anhydrous ethanol, add 10g of phosphoric acid after mixing evenly, stir and react for 8h, filter, wash and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 25g of anhydrous ethanol, add 8g of polysiloxane, stir and react for 8h, filter, wash and dry after the reaction to prepare a composite flame retardant;
[0033] Step 5: Mix 100 g of epoxy resin, 20 g of composite flame retardant, 15 g of core-shell toughening filler, 10 g of methyl nadic anhydride, 0.03 g of 2-phenylimidazole and 30 g of acetone, and stir at high speed for 8 hours to prepare a finished product.
[0034] Example 2: Step 1: 150 g of n-butyl acrylate, 3 g of sodium dodecyl diphenyl oxide disulfonate and 0.7 g of allyl methacrylate are mixed to prepare a core layer pre-emulsion; 40 g of methyl methacrylate monomer, 0.8 g of sodium dodecyl diphenyl oxide disulfonate and 1 g of acrylamide are mixed to prepare a shell layer pre-emulsion; 0.8 g of potassium persulfate and 100 g of deionized water are mixed to prepare an initiator;
[0035] In an argon environment, 0.5 g of sodium dodecyl diphenyl ether disulfonate and 150 g of deionized water were mixed, and after stirring, 10 g of n-butyl acrylate and 0.06 g of 1,4-butanediol diacrylate were added, and after stirring, 20 g of initiator was added, and after reacting for 1.5 hours, 10 g of initiator was added, and the reaction was continued for 13 minutes to obtain a seed polymerization emulsion; 153.7 g of the core layer pre-emulsion and 30 g of the initiator were added dropwise to the seed polymerization emulsion, and the reaction time was 2.5 hours. After the addition was completed, 41.8 g of the shell layer pre-emulsion and 60 g of the initiator were added dropwise, and the reaction time was 3.5 hours. After the reaction was completed, it was cooled, filtered, and low-temperature dried to prepare a core-shell toughened filler;
[0036] Step 2: Under a nitrogen environment, 0.1 mol of 1,3,5-trialdehyde-1,3,5-triazine, 0.4 mol of (3-aminopropyl)triethoxysilane and 300 ml of anhydrous ethanol were mixed, stirred at 65°C for 1.5 hours, and then subjected to rotary evaporation and vacuum drying to prepare a silane intermediate; under a nitrogen environment, the silane intermediate, 0.3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 300 ml of anhydrous ethanol were mixed, stirred at 95°C for 5 hours to prepare a modified silane;
[0037] Step 3: Under a nitrogen environment, 20 g of modified silane, 15 g of dimethyldimethoxysilane and 20 g of deionized water were mixed, refluxed at 27 ° C for 2.5 h, heated to 95 ° C for 5.3 h, and cooled to 27 ° C after the reaction to obtain a hydrolyzate; then 0.5 g of potassium hydroxide and 0.4 g of hexamethyldisiloxane were added, and the reaction was carried out at 105 ° C for 11 h. After the reaction, 0.8 g of acetic acid was added dropwise to neutralize and remove low-boiling products to prepare polysiloxane;
[0038] Step 4: Mix 15g of aluminum hydroxide powder and 15g of anhydrous ethanol, add 10g of phosphoric acid after mixing evenly, stir and react for 7h, filter, wash and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 25g of anhydrous ethanol, add 8g of polysiloxane, stir and react for 6h, filter, wash and dry after the reaction to prepare a composite flame retardant;
[0039] Step 5: Mix 100 g of epoxy resin, 20 g of composite flame retardant, 15 g of core-shell toughening filler, 10 g of methyl nadic anhydride, 0.03 g of 2-phenylimidazole and 30 g of acetone, and stir at high speed for 7 hours to prepare a finished product.
[0040] Example 3: Step 1: 150 g of n-butyl acrylate, 3 g of sodium dodecyl diphenyl oxide disulfonate and 0.7 g of allyl methacrylate are mixed to prepare a core layer pre-emulsion; 40 g of methyl methacrylate monomer, 0.8 g of sodium dodecyl diphenyl oxide disulfonate and 1 g of acrylamide are mixed to prepare a shell layer pre-emulsion; 0.8 g of potassium persulfate and 100 g of deionized water are mixed to prepare an initiator;
[0041] In an argon environment, 0.5 g of sodium dodecyl diphenyl ether disulfonate and 150 g of deionized water were mixed, and 10 g of n-butyl acrylate and 0.06 g of 1,4-butanediol diacrylate were added after stirring, and 20 g of initiator was added after stirring. After reacting for 1 hour, 10 g of initiator was added, and the reaction was continued for 10 minutes to obtain a seed polymerization emulsion; 153.7 g of the core layer pre-emulsion and 30 g of the initiator were added dropwise to the seed polymerization emulsion, and the reaction time was 2 hours. After the addition was completed, 41.8 g of the shell layer pre-emulsion and 60 g of the initiator were added dropwise, and the reaction time was 3 hours. After the reaction was completed, it was cooled, filtered, and low-temperature dried to prepare a core-shell toughened filler;
[0042] Step 2: Under a nitrogen environment, 0.1 mol of 1,3,5-trialdehyde-1,3,5-triazine, 0.4 mol of (3-aminopropyl)triethoxysilane and 300 ml of anhydrous ethanol were mixed, stirred at 60°C for 1 hour, and then subjected to rotary evaporation and vacuum drying to prepare a silane intermediate; under a nitrogen environment, the silane intermediate, 0.3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 300 ml of anhydrous ethanol were mixed, stirred at 90°C for 4 hours to prepare a modified silane;
[0043] Step 3: Under a nitrogen environment, 20 g of modified silane, 15 g of dimethyldimethoxysilane and 20 g of deionized water were mixed, refluxed at 25 ° C for 2 h, heated to 90 ° C for 5 h, and cooled to 25 ° C after the reaction to obtain a hydrolyzate; then 0.5 g of potassium hydroxide and 0.4 g of hexamethyldisiloxane were added, and the reaction was carried out at 100 ° C for 10 h. After the reaction, 0.8 g of acetic acid was added dropwise to neutralize and remove low-boiling products to prepare polysiloxane;
[0044] Step 4: Mix 15g of aluminum hydroxide powder and 15g of anhydrous ethanol, add 10g of phosphoric acid after mixing evenly, stir and react for 6h, filter, wash and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 25g of anhydrous ethanol, add 8g of polysiloxane, stir and react for 5h, filter, wash and dry after the reaction to prepare a composite flame retardant;
[0045] Step 5: Mix 100 g of epoxy resin, 20 g of composite flame retardant, 15 g of core-shell toughening filler, 10 g of methyl nadic anhydride, 0.03 g of 2-phenylimidazole and 30 g of acetone, and stir at high speed for 6 hours to prepare a finished product.
[0046] Comparative Example 1: The preparation step of the core-shell toughening filler is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Under a nitrogen environment, 0.1 mol of 1,3,5-trialdehyde-1,3,5-triazine, 0.4 mol of (3-aminopropyl)triethoxysilane and 300 ml of anhydrous ethanol are mixed, stirred at 70°C for 2 hours, and then subjected to rotary evaporation and vacuum drying to prepare a silane intermediate; Under a nitrogen environment, the silane intermediate, 0.3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 300 ml of anhydrous ethanol are mixed, stirred at 100°C for 6 hours to prepare a modified silane;
[0047] Step 2: Under a nitrogen environment, 20 g of modified silane, 15 g of dimethyldimethoxysilane and 20 g of deionized water were mixed, refluxed at 30 ° C for 3 h, heated to 100 ° C and continued to react for 5.5 h, and cooled to 25 ° C after the reaction to obtain a hydrolyzate; then 0.5 g of potassium hydroxide and 0.4 g of hexamethyldisiloxane were added, and the reaction was carried out at 110 ° C for 12 h. After the reaction, 0.8 g of acetic acid was added dropwise to neutralize and remove low-boiling products to prepare polysiloxane;
[0048] Step 3: Mix 15g of aluminum hydroxide powder and 15g of anhydrous ethanol, add 10g of phosphoric acid after mixing evenly, stir to react for 8h, filter, wash and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 25g of anhydrous ethanol, add 8g of polysiloxane, stir to react for 8h, filter, wash and dry after the reaction to prepare a composite flame retardant;
[0049] Step 4: Mix 100 g of epoxy resin, 20 g of composite flame retardant, 10 g of methyl nadic anhydride, 0.03 g of 2-phenylimidazole and 30 g of acetone, and stir at high speed for 8 hours to prepare a finished product.
[0050] Comparative Example 2: The preparation step of polysiloxane is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 150g of n-butyl acrylate, 3g of sodium dodecyl diphenyl oxide disulfonate and 0.7g of allyl methacrylate are mixed to prepare a core layer pre-emulsion; 40g of methyl methacrylate monomer, 0.8g of sodium dodecyl diphenyl oxide disulfonate and 1g of acrylamide are mixed to prepare a shell layer pre-emulsion; 0.8g of potassium persulfate and 100g of deionized water are mixed to prepare an initiator;
[0051] In an argon environment, 0.5 g of sodium dodecyl diphenyl ether disulfonate and 150 g of deionized water were mixed, and after stirring, 10 g of n-butyl acrylate and 0.06 g of 1,4-butanediol diacrylate were added, and after stirring, 20 g of initiator was added, and after reacting for 2 hours, 10 g of initiator was added, and the reaction was continued for 15 minutes to obtain a seed polymerization emulsion; 153.7 g of the core layer pre-emulsion and 30 g of the initiator were added dropwise to the seed polymerization emulsion, and the reaction time was 3 hours. After the addition was completed, 41.8 g of the shell layer pre-emulsion and 60 g of the initiator were added dropwise, and the reaction time was 4 hours. After the reaction was completed, it was cooled, filtered, and low-temperature dried to prepare a core-shell toughened filler;
[0052] Step 2: 15 g of aluminum hydroxide powder and 15 g of anhydrous ethanol were mixed, 10 g of phosphoric acid was added after mixing evenly, and the mixture was stirred for 8 h, and then filtered, washed, and dried to prepare a core-shell flame retardant;
[0053] Step 3: Mix 100 g of epoxy resin, 20 g of core-shell flame retardant, 15 g of core-shell toughening filler, 10 g of methyl nadic anhydride, 0.03 g of 2-phenylimidazole and 30 g of acetone, and stir at high speed for 8 hours to prepare a finished product.
[0054] Detection test:
[0055] Tensile strength test: the finished product prepared by the present invention is placed in a mold and cured at 200°C for 5 minutes to obtain a sample. According to GB / T 1040-1992 "Plastic Tensile Properties Test Method", the sample size is based on type III sample, the experimental tensile speed is 5mm / min±10%, three points are measured for each sample, the arithmetic average is taken, and finally the tensile strength is calculated by the formula.
[0056] Oxygen index performance test: The finished product prepared by the present invention is placed in a mold and cured at 200°C for 5 minutes to obtain a sample. According to GB / T 2406-1993 standard, the sample size is 80×10×4mm, the initial oxygen concentration is 21%, and a mixed gas of oxygen and nitrogen is introduced in an environment at 25°C. Then, the oxygen index is calculated using a formula. The larger the oxygen index, the better the flame retardant performance. The results are shown in the following table;
[0057] Tensile strength / MPa Oxygen index / % Example 1 93.5 35 Example 2 93.4 34 Example 3 93.3 33 Comparative Example 1 82.3 33 Comparative Example 2 91.0 29
[0058] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. It can be seen from the experimental data that there is no obvious fluctuation in the various properties of the samples. Comparative Example 1: The preparation steps of the core-shell toughening filler are removed, and the rest are the same as Example 1. It can be seen from the experimental data that compared with Example 1, the tensile strength is reduced to 82.3MPa, and the oxygen index is 33%. The reason for analysis is: the core-shell toughening filler prepared by the present invention is a high-strength filling material, which can significantly improve the toughness and mechanical properties of epoxy resin. Therefore, after the preparation of the core-shell toughening filler is removed, the tensile strength will be reduced.
[0059] Comparative Example 2: The preparation step of polysiloxane is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the tensile strength is reduced to 91.0 MPa, and the oxygen index is 29%. The reasons are analyzed as follows: the polysiloxane prepared by the present invention contains a large amount of nitrogen, phosphorus and silicon elements, among which nitrogen and phosphorus can effectively improve the flame retardant properties of the material, reduce the combustion rate and flame propagation; silicon has lower flammability and higher thermal stability, and can prevent or delay the combustion process; therefore, after removing the polysiloxane, the flame retardant properties of the sample are reduced, and the oxygen index is reduced.
[0060] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an epoxy resin filled with aluminum hydroxide for a copper clad laminate, characterized in that: The following steps are involved: Step 1: Under an argon environment, mix the emulsifier and deionized water, stir evenly, then add n-butyl acrylate and 1,4-butanediol diacrylate, stir evenly, then add 1 / 6 mass part of initiator, react for 1-2 hours, then add 1 / 12 mass part of initiator, continue to react for 10-15 minutes, and obtain a seed polymerization emulsion; then drop the core layer pre-emulsion and 1 / 4 mass part of initiator into the seed polymerization emulsion, and the reaction time is 2-3 hours; after the dropwise addition, drop the shell layer pre-emulsion and 1 / 2 mass part of initiator, and the reaction time is 3-4 hours. After the reaction is completed, cool, filter, and dry at low temperature to prepare a core-shell toughened filler; The core layer pre-emulsion is composed of 150-180 parts of n-butyl acrylate, 3-5 parts of emulsifier and 0.7-0.9 parts of cross-linking agent; the shell layer pre-emulsion is composed of 40-50 parts of methyl methacrylate monomer, 0.8-1.0 parts of emulsifier and 1-2 parts of functional monomer; the initiator is a mixture of potassium persulfate and deionized water, the mass ratio is (0.08-0.10):10; the cross-linking agent is allyl methacrylate; the functional monomer acrylamide; the emulsifier is sodium dodecyl diphenyl ether disulfonate; the contents of the components of the core-shell toughening filler are: by mass, 0.5-0.8 parts of emulsifier, 150-200 parts of deionized water, 10-15 parts of n-butyl acrylate, 0.06-0.08 parts of 1,4-butanediol diacrylate, 120-480 parts of initiator, 153.7-185.9 parts of core layer pre-emulsion, and 41.8-53.0 parts of shell layer pre-emulsion; Step 2: The preparation method of modified silane is as follows: in a nitrogen environment, 1,3,5-trialdehyde-1,3,5-triazine, (3-aminopropyl) triethoxysilane and anhydrous ethanol are mixed, stirred at 60-70°C for reaction for 1-2h, and then subjected to rotary evaporation and vacuum drying to prepare a silane intermediate; in a nitrogen environment, the silane intermediate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and anhydrous ethanol are mixed, stirred at 90-100°C for reaction for 4-6h to prepare a modified silane; the reaction molar ratio of 1,3,5-trialdehyde-1,3,5-triazine, (3-aminopropyl) triethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:(4-5):3; In a nitrogen environment, the modified silane, dimethyldimethoxysilane and deionized water are mixed, refluxed at 25-30°C for 2-3h, heated to 90-100°C for 5-5.5h, and cooled to 25-30°C after the reaction to obtain a hydrolyzate; a catalyst and a capping agent are added, and the reaction is carried out at 100-110°C for 10-12h. After the reaction is completed, acetic acid is added dropwise for neutralization and low-boiling products are removed to prepare polysiloxane; wherein the content of each component of the polysiloxane is: by mass, 20-40 parts of modified silane, 15-20 parts of dimethyldimethoxysilane, 20-40 parts of deionized water, 0.5-0.8 parts of catalyst, 0.4-0.6 parts of capping agent, and 0.8-1.0 parts of acetic acid; the catalyst is potassium hydroxide, and the capping agent is hexamethyldisiloxane; Step 3: Mix aluminum hydroxide powder and 3 / 8 parts by weight of anhydrous ethanol, add phosphoric acid after mixing evenly, stir to react for 6-8 hours, filter, wash, and dry to prepare a core-shell flame retardant; fully mix the core-shell flame retardant and 5 / 8 parts by weight of anhydrous ethanol, add polysiloxane, stir to react for 5-8 hours, filter, wash, and dry after the reaction to prepare a composite flame retardant; The contents of the composite flame retardant components are as follows: by mass: 15-20 parts of aluminum hydroxide powder, 40-70 parts of anhydrous ethanol, 10-15 parts of phosphoric acid, and 8-15 parts of polysiloxane; Step 4: Mix the epoxy resin, composite flame retardant, core-shell toughening filler, curing agent, curing accelerator and solvent, and stir at high speed for 6-8 hours to prepare a finished product.
2. The method for preparing an epoxy resin filled with aluminum hydroxide for copper clad laminate according to claim 1, characterized in that: In step 4, the contents of the components of the finished product are: by mass, 100-150 parts of epoxy resin, 20-30 parts of composite flame retardant, 15-25 parts of core-shell toughening filler, 10-15 parts of curing agent, 0.03-0.05 parts of curing accelerator, and 30-50 parts of solvent.
3. The method for preparing an epoxy resin filled with aluminum hydroxide for copper clad laminate according to claim 2, characterized in that: The curing agent is methyl nadic anhydride, the curing accelerator is 2-phenylimidazole, and the solvent is acetone.
Citation Information
Patent Citations
Fiber reinforced composite material and preparation method thereof
CN109438918A
Structural flame-retardant functional composite material and preparation method thereof
CN112009038A